Excitation‐Dependent Emission in All‐Inorganic Lead‐Free Cs2ScCl5·H2O Perovskite Crystals. Issue 5 (5th February 2022) - Zhang, Ruiling; Xu, Xin; Mao, Xin; Wang, Zhongyi; Wang, Pengyuan; Yang, Yang; Chen, Junsheng; Lu, Ruifeng; Deng, Weiqiao; Han, Keli
Abstract: Low‐dimensional lead‐free metal halides have recently attracted a great deal of attention for their unique photoluminescence properties. In this work, a new all‐inorganic zero‐dimensional (0D) rare‐earth perovskite, namely Cs2 ScCl5 ·H2 O is reported. The 0D crystal exhibits a rare phenomenon of excitation‐wavelength dependent emission from blue‐green to white to yellow at room temperature. Spectroscopic characterizations indicate the tunable emission is originated from two distinct self‐trapped exciton states. In addition, the yellow emission quantum yield can be enhanced from 1.2% to ≈100% by doping Sb 3+ ions into the crystal. The work not only presents a new all‐inorganic semiconductor with tunable emission colors, but also provides a design strategy for developing nontoxic and high‐performance light‐emitting materials. Abstract : A zero‐dimensional rare‐earth metal halide Cs2 ScCl5 ·H2 O with unusual excitation‐dependent emission behavior is reported. The emission color can be tuned from blue‐green to white to yellow by changing excitation wavelengths. The tunable emission is originated from two different self‐trapped exciton states. Furthermore, Sb 3+ ions are successfully doped into Cs2 ScCl5 ·H2 O crystals, leading to about 100% yellow photoluminescence quantum yield.